2017
DOI: 10.1038/srep41513
|View full text |Cite
|
Sign up to set email alerts
|

A de novo deletion mutation in SOX10 in a Chinese family with Waardenburg syndrome type 4

Abstract: Waardenburg syndrome type 4 (WS4) or Waardenburg-Shah syndrome is a rare genetic disorder with a prevalence of <1/1,000,000 and characterized by the association of congenital sensorineural hearing loss, pigmentary abnormalities, and intestinal aganglionosis. There are three types of WS4 (WS4A–C) caused by mutations in endothelin receptor type B, endothelin 3, and SRY-box 10 (SOX10), respectively. This study investigated a genetic mutation in a Chinese family with one WS4 patient in order to improve genetic cou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…However, the subjects were prepubertal and formal testing for anosmia was not reported. Interestingly, SOX10 mutations, unlike PAX3 mutations, most commonly arise de‐novo, which may be related to infertility . Future studies focusing on genotype should include a comprehensive phenotype profile and, if appropriate, long‐term follow‐up.…”
Section: Perspectives Areas Of Uncertainty and Conclusionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the subjects were prepubertal and formal testing for anosmia was not reported. Interestingly, SOX10 mutations, unlike PAX3 mutations, most commonly arise de‐novo, which may be related to infertility . Future studies focusing on genotype should include a comprehensive phenotype profile and, if appropriate, long‐term follow‐up.…”
Section: Perspectives Areas Of Uncertainty and Conclusionmentioning
confidence: 99%
“…Interestingly, SOX10 mutations, unlike PAX3 mutations, most commonly arise de-novo, which may be related to infertility. [110][111][112] All neonates born to parents with CHH should be formally evaluated by an endocrinologist. Referral should not be delayed because the window for hormone profiling is narrow.…”
Section: Saleemmentioning
confidence: 99%
“…The four types of WS exhibit common phenotypes and differences. Compared with WS1, the inner canthi of both eyes in patients with WS2 were normal, those with WS3 exhibit upper limb abnormalities, and those with WS type IV (WS4) had Hirschsprung disease (Wang et al, 2017 ; Ahmed Jan et al, 2021 ). Symptoms in I:1 and II:3 were more consistent with those in WS3, whereas II:2 was diagnosed with WS1.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, through analysis of the reported cases and the literature, we found that when the SOX10 mutation site occurred behind the 180th amino acid, or you could say after the HMG domain, it caused more severe symptoms of type IV WS [ 5 , 6 , 36 39 ] ( Table 2 ). We speculate that the reason may be due to the truncated mutation which means that the HMG domain loses the normal function of the protein, but can combine with the target gene promoter.…”
Section: Discussionmentioning
confidence: 99%
“…The clinical manifestations of type II are basically the same as type I, but without dystopia of the canthus. The clinical manifestations of type III are the same as type I, but combined with upper limb deformity, while type IV exhibits basically the same symptoms as type II, but combined with Hirschsprung disease (gastrointestinal malformation) [3][4][5][6]. Mutations of the PAX3, SOX10, MITF, SNAI2, EDNRB, and EDN3 genes have been found in cases of the different types of WS [7,8].…”
Section: Introductionmentioning
confidence: 99%